src/HOL/Semiring_Normalization.thy
author haftmann
Fri May 07 16:12:26 2010 +0200 (2010-05-07)
changeset 36753 5cf4e9128f22
parent 36751 7f1da69cacb3
child 36756 c1ae8a0b4265
permissions -rw-r--r--
renamed Normalizer to the more specific Semiring_Normalizer
haftmann@36751
     1
(*  Title:      HOL/Semiring_Normalization.thy
wenzelm@23252
     2
    Author:     Amine Chaieb, TU Muenchen
wenzelm@23252
     3
*)
wenzelm@23252
     4
haftmann@36751
     5
header {* Semiring normalization *}
haftmann@28402
     6
haftmann@36751
     7
theory Semiring_Normalization
haftmann@36699
     8
imports Numeral_Simprocs Nat_Transfer
wenzelm@23252
     9
uses
haftmann@36753
    10
  "Tools/semiring_normalizer.ML"
wenzelm@23252
    11
begin
wenzelm@23252
    12
haftmann@36753
    13
setup Semiring_Normalizer.setup
wenzelm@23252
    14
haftmann@36712
    15
locale normalizing_semiring =
wenzelm@23252
    16
  fixes add mul pwr r0 r1
wenzelm@23252
    17
  assumes add_a:"(add x (add y z) = add (add x y) z)"
wenzelm@23252
    18
    and add_c: "add x y = add y x" and add_0:"add r0 x = x"
wenzelm@23252
    19
    and mul_a:"mul x (mul y z) = mul (mul x y) z" and mul_c:"mul x y = mul y x"
wenzelm@23252
    20
    and mul_1:"mul r1 x = x" and  mul_0:"mul r0 x = r0"
wenzelm@23252
    21
    and mul_d:"mul x (add y z) = add (mul x y) (mul x z)"
wenzelm@23252
    22
    and pwr_0:"pwr x 0 = r1" and pwr_Suc:"pwr x (Suc n) = mul x (pwr x n)"
wenzelm@23252
    23
begin
wenzelm@23252
    24
wenzelm@23252
    25
lemma mul_pwr:"mul (pwr x p) (pwr x q) = pwr x (p + q)"
wenzelm@23252
    26
proof (induct p)
wenzelm@23252
    27
  case 0
wenzelm@23252
    28
  then show ?case by (auto simp add: pwr_0 mul_1)
wenzelm@23252
    29
next
wenzelm@23252
    30
  case Suc
wenzelm@23252
    31
  from this [symmetric] show ?case
wenzelm@23252
    32
    by (auto simp add: pwr_Suc mul_1 mul_a)
wenzelm@23252
    33
qed
wenzelm@23252
    34
wenzelm@23252
    35
lemma pwr_mul: "pwr (mul x y) q = mul (pwr x q) (pwr y q)"
wenzelm@23252
    36
proof (induct q arbitrary: x y, auto simp add:pwr_0 pwr_Suc mul_1)
wenzelm@23252
    37
  fix q x y
wenzelm@23252
    38
  assume "\<And>x y. pwr (mul x y) q = mul (pwr x q) (pwr y q)"
wenzelm@23252
    39
  have "mul (mul x y) (mul (pwr x q) (pwr y q)) = mul x (mul y (mul (pwr x q) (pwr y q)))"
wenzelm@23252
    40
    by (simp add: mul_a)
wenzelm@23252
    41
  also have "\<dots> = (mul (mul y (mul (pwr y q) (pwr x q))) x)" by (simp add: mul_c)
wenzelm@23252
    42
  also have "\<dots> = (mul (mul y (pwr y q)) (mul (pwr x q) x))" by (simp add: mul_a)
wenzelm@23252
    43
  finally show "mul (mul x y) (mul (pwr x q) (pwr y q)) =
wenzelm@23252
    44
    mul (mul x (pwr x q)) (mul y (pwr y q))" by (simp add: mul_c)
wenzelm@23252
    45
qed
wenzelm@23252
    46
wenzelm@23252
    47
lemma pwr_pwr: "pwr (pwr x p) q = pwr x (p * q)"
wenzelm@23252
    48
proof (induct p arbitrary: q)
wenzelm@23252
    49
  case 0
wenzelm@23252
    50
  show ?case using pwr_Suc mul_1 pwr_0 by (induct q) auto
wenzelm@23252
    51
next
wenzelm@23252
    52
  case Suc
wenzelm@23252
    53
  thus ?case by (auto simp add: mul_pwr [symmetric] pwr_mul pwr_Suc)
wenzelm@23252
    54
qed
wenzelm@23252
    55
wenzelm@23252
    56
lemma semiring_ops:
wenzelm@23252
    57
  shows "TERM (add x y)" and "TERM (mul x y)" and "TERM (pwr x n)"
wenzelm@28856
    58
    and "TERM r0" and "TERM r1" .
wenzelm@23252
    59
wenzelm@23252
    60
lemma semiring_rules:
wenzelm@23252
    61
  "add (mul a m) (mul b m) = mul (add a b) m"
wenzelm@23252
    62
  "add (mul a m) m = mul (add a r1) m"
wenzelm@23252
    63
  "add m (mul a m) = mul (add a r1) m"
wenzelm@23252
    64
  "add m m = mul (add r1 r1) m"
wenzelm@23252
    65
  "add r0 a = a"
wenzelm@23252
    66
  "add a r0 = a"
wenzelm@23252
    67
  "mul a b = mul b a"
wenzelm@23252
    68
  "mul (add a b) c = add (mul a c) (mul b c)"
wenzelm@23252
    69
  "mul r0 a = r0"
wenzelm@23252
    70
  "mul a r0 = r0"
wenzelm@23252
    71
  "mul r1 a = a"
wenzelm@23252
    72
  "mul a r1 = a"
wenzelm@23252
    73
  "mul (mul lx ly) (mul rx ry) = mul (mul lx rx) (mul ly ry)"
wenzelm@23252
    74
  "mul (mul lx ly) (mul rx ry) = mul lx (mul ly (mul rx ry))"
wenzelm@23252
    75
  "mul (mul lx ly) (mul rx ry) = mul rx (mul (mul lx ly) ry)"
wenzelm@23252
    76
  "mul (mul lx ly) rx = mul (mul lx rx) ly"
wenzelm@23252
    77
  "mul (mul lx ly) rx = mul lx (mul ly rx)"
wenzelm@23252
    78
  "mul lx (mul rx ry) = mul (mul lx rx) ry"
wenzelm@23252
    79
  "mul lx (mul rx ry) = mul rx (mul lx ry)"
wenzelm@23252
    80
  "add (add a b) (add c d) = add (add a c) (add b d)"
wenzelm@23252
    81
  "add (add a b) c = add a (add b c)"
wenzelm@23252
    82
  "add a (add c d) = add c (add a d)"
wenzelm@23252
    83
  "add (add a b) c = add (add a c) b"
wenzelm@23252
    84
  "add a c = add c a"
wenzelm@23252
    85
  "add a (add c d) = add (add a c) d"
wenzelm@23252
    86
  "mul (pwr x p) (pwr x q) = pwr x (p + q)"
wenzelm@23252
    87
  "mul x (pwr x q) = pwr x (Suc q)"
wenzelm@23252
    88
  "mul (pwr x q) x = pwr x (Suc q)"
wenzelm@23252
    89
  "mul x x = pwr x 2"
wenzelm@23252
    90
  "pwr (mul x y) q = mul (pwr x q) (pwr y q)"
wenzelm@23252
    91
  "pwr (pwr x p) q = pwr x (p * q)"
wenzelm@23252
    92
  "pwr x 0 = r1"
wenzelm@23252
    93
  "pwr x 1 = x"
wenzelm@23252
    94
  "mul x (add y z) = add (mul x y) (mul x z)"
wenzelm@23252
    95
  "pwr x (Suc q) = mul x (pwr x q)"
wenzelm@23252
    96
  "pwr x (2*n) = mul (pwr x n) (pwr x n)"
wenzelm@23252
    97
  "pwr x (Suc (2*n)) = mul x (mul (pwr x n) (pwr x n))"
wenzelm@23252
    98
proof -
wenzelm@23252
    99
  show "add (mul a m) (mul b m) = mul (add a b) m" using mul_d mul_c by simp
wenzelm@23252
   100
next show"add (mul a m) m = mul (add a r1) m" using mul_d mul_c mul_1 by simp
wenzelm@23252
   101
next show "add m (mul a m) = mul (add a r1) m" using mul_c mul_d mul_1 add_c by simp
wenzelm@23252
   102
next show "add m m = mul (add r1 r1) m" using mul_c mul_d mul_1 by simp
wenzelm@23252
   103
next show "add r0 a = a" using add_0 by simp
wenzelm@23252
   104
next show "add a r0 = a" using add_0 add_c by simp
wenzelm@23252
   105
next show "mul a b = mul b a" using mul_c by simp
wenzelm@23252
   106
next show "mul (add a b) c = add (mul a c) (mul b c)" using mul_c mul_d by simp
wenzelm@23252
   107
next show "mul r0 a = r0" using mul_0 by simp
wenzelm@23252
   108
next show "mul a r0 = r0" using mul_0 mul_c by simp
wenzelm@23252
   109
next show "mul r1 a = a" using mul_1 by simp
wenzelm@23252
   110
next show "mul a r1 = a" using mul_1 mul_c by simp
wenzelm@23252
   111
next show "mul (mul lx ly) (mul rx ry) = mul (mul lx rx) (mul ly ry)"
wenzelm@23252
   112
    using mul_c mul_a by simp
wenzelm@23252
   113
next show "mul (mul lx ly) (mul rx ry) = mul lx (mul ly (mul rx ry))"
wenzelm@23252
   114
    using mul_a by simp
wenzelm@23252
   115
next
wenzelm@23252
   116
  have "mul (mul lx ly) (mul rx ry) = mul (mul rx ry) (mul lx ly)" by (rule mul_c)
wenzelm@23252
   117
  also have "\<dots> = mul rx (mul ry (mul lx ly))" using mul_a by simp
wenzelm@23252
   118
  finally
wenzelm@23252
   119
  show "mul (mul lx ly) (mul rx ry) = mul rx (mul (mul lx ly) ry)"
wenzelm@23252
   120
    using mul_c by simp
wenzelm@23252
   121
next show "mul (mul lx ly) rx = mul (mul lx rx) ly" using mul_c mul_a by simp
wenzelm@23252
   122
next
wenzelm@23252
   123
  show "mul (mul lx ly) rx = mul lx (mul ly rx)" by (simp add: mul_a)
wenzelm@23252
   124
next show "mul lx (mul rx ry) = mul (mul lx rx) ry" by (simp add: mul_a )
wenzelm@23252
   125
next show "mul lx (mul rx ry) = mul rx (mul lx ry)" by (simp add: mul_a,simp add: mul_c)
wenzelm@23252
   126
next show "add (add a b) (add c d) = add (add a c) (add b d)"
wenzelm@23252
   127
    using add_c add_a by simp
wenzelm@23252
   128
next show "add (add a b) c = add a (add b c)" using add_a by simp
wenzelm@23252
   129
next show "add a (add c d) = add c (add a d)"
wenzelm@23252
   130
    apply (simp add: add_a) by (simp only: add_c)
wenzelm@23252
   131
next show "add (add a b) c = add (add a c) b" using add_a add_c by simp
wenzelm@23252
   132
next show "add a c = add c a" by (rule add_c)
wenzelm@23252
   133
next show "add a (add c d) = add (add a c) d" using add_a by simp
wenzelm@23252
   134
next show "mul (pwr x p) (pwr x q) = pwr x (p + q)" by (rule mul_pwr)
wenzelm@23252
   135
next show "mul x (pwr x q) = pwr x (Suc q)" using pwr_Suc by simp
wenzelm@23252
   136
next show "mul (pwr x q) x = pwr x (Suc q)" using pwr_Suc mul_c by simp
huffman@35216
   137
next show "mul x x = pwr x 2" by (simp add: nat_number' pwr_Suc pwr_0 mul_1 mul_c)
wenzelm@23252
   138
next show "pwr (mul x y) q = mul (pwr x q) (pwr y q)" by (rule pwr_mul)
wenzelm@23252
   139
next show "pwr (pwr x p) q = pwr x (p * q)" by (rule pwr_pwr)
wenzelm@23252
   140
next show "pwr x 0 = r1" using pwr_0 .
huffman@35216
   141
next show "pwr x 1 = x" unfolding One_nat_def by (simp add: nat_number' pwr_Suc pwr_0 mul_1 mul_c)
wenzelm@23252
   142
next show "mul x (add y z) = add (mul x y) (mul x z)" using mul_d by simp
wenzelm@23252
   143
next show "pwr x (Suc q) = mul x (pwr x q)" using pwr_Suc by simp
huffman@35216
   144
next show "pwr x (2 * n) = mul (pwr x n) (pwr x n)" by (simp add: nat_number' mul_pwr)
wenzelm@23252
   145
next show "pwr x (Suc (2 * n)) = mul x (mul (pwr x n) (pwr x n))"
huffman@35216
   146
    by (simp add: nat_number' pwr_Suc mul_pwr)
wenzelm@23252
   147
qed
wenzelm@23252
   148
wenzelm@23252
   149
haftmann@36712
   150
lemmas normalizing_semiring_axioms' =
haftmann@36712
   151
  normalizing_semiring_axioms [normalizer
wenzelm@23252
   152
    semiring ops: semiring_ops
wenzelm@26314
   153
    semiring rules: semiring_rules]
wenzelm@23252
   154
wenzelm@23252
   155
end
wenzelm@23252
   156
haftmann@36712
   157
sublocale comm_semiring_1
haftmann@36712
   158
  < normalizing!: normalizing_semiring plus times power zero one
haftmann@36712
   159
proof
haftmann@36712
   160
qed (simp_all add: algebra_simps)
wenzelm@23252
   161
haftmann@36753
   162
declaration {* Semiring_Normalizer.semiring_funs @{thm normalizing.normalizing_semiring_axioms'} *}
wenzelm@23573
   163
haftmann@36712
   164
locale normalizing_ring = normalizing_semiring +
wenzelm@23252
   165
  fixes sub :: "'a \<Rightarrow> 'a \<Rightarrow> 'a"
wenzelm@23252
   166
    and neg :: "'a \<Rightarrow> 'a"
wenzelm@23252
   167
  assumes neg_mul: "neg x = mul (neg r1) x"
wenzelm@23252
   168
    and sub_add: "sub x y = add x (neg y)"
wenzelm@23252
   169
begin
wenzelm@23252
   170
wenzelm@28856
   171
lemma ring_ops: shows "TERM (sub x y)" and "TERM (neg x)" .
wenzelm@23252
   172
wenzelm@23252
   173
lemmas ring_rules = neg_mul sub_add
wenzelm@23252
   174
haftmann@36712
   175
lemmas normalizing_ring_axioms' =
haftmann@36712
   176
  normalizing_ring_axioms [normalizer
wenzelm@26314
   177
    semiring ops: semiring_ops
wenzelm@26314
   178
    semiring rules: semiring_rules
wenzelm@26314
   179
    ring ops: ring_ops
wenzelm@26314
   180
    ring rules: ring_rules]
wenzelm@23252
   181
wenzelm@23252
   182
end
wenzelm@23252
   183
haftmann@36720
   184
sublocale comm_ring_1
haftmann@36720
   185
  < normalizing!: normalizing_ring plus times power zero one minus uminus
haftmann@36720
   186
proof
haftmann@36720
   187
qed (simp_all add: diff_minus)
wenzelm@23252
   188
haftmann@36753
   189
declaration {* Semiring_Normalizer.semiring_funs @{thm normalizing.normalizing_ring_axioms'} *}
wenzelm@23252
   190
haftmann@36712
   191
locale normalizing_field = normalizing_ring +
chaieb@23327
   192
  fixes divide :: "'a \<Rightarrow> 'a \<Rightarrow> 'a"
chaieb@23327
   193
    and inverse:: "'a \<Rightarrow> 'a"
chaieb@30866
   194
  assumes divide_inverse: "divide x y = mul x (inverse y)"
chaieb@30866
   195
     and inverse_divide: "inverse x = divide r1 x"
chaieb@23327
   196
begin
chaieb@23327
   197
chaieb@30866
   198
lemma field_ops: shows "TERM (divide x y)" and "TERM (inverse x)" .
chaieb@30866
   199
chaieb@30866
   200
lemmas field_rules = divide_inverse inverse_divide
chaieb@30866
   201
haftmann@36712
   202
lemmas normalizing_field_axioms' =
haftmann@36712
   203
  normalizing_field_axioms [normalizer
wenzelm@26314
   204
    semiring ops: semiring_ops
wenzelm@26314
   205
    semiring rules: semiring_rules
wenzelm@26314
   206
    ring ops: ring_ops
chaieb@30866
   207
    ring rules: ring_rules
chaieb@30866
   208
    field ops: field_ops
chaieb@30866
   209
    field rules: field_rules]
chaieb@23327
   210
chaieb@23327
   211
end
chaieb@23327
   212
haftmann@36712
   213
locale normalizing_semiring_cancel = normalizing_semiring +
wenzelm@23252
   214
  assumes add_cancel: "add (x::'a) y = add x z \<longleftrightarrow> y = z"
wenzelm@23252
   215
  and add_mul_solve: "add (mul w y) (mul x z) =
wenzelm@23252
   216
    add (mul w z) (mul x y) \<longleftrightarrow> w = x \<or> y = z"
wenzelm@23252
   217
begin
wenzelm@23252
   218
wenzelm@23252
   219
lemma noteq_reduce: "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
wenzelm@23252
   220
proof-
wenzelm@23252
   221
  have "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> \<not> (a = b \<or> c = d)" by simp
wenzelm@23252
   222
  also have "\<dots> \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
wenzelm@23252
   223
    using add_mul_solve by blast
wenzelm@23252
   224
  finally show "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
wenzelm@23252
   225
    by simp
wenzelm@23252
   226
qed
wenzelm@23252
   227
wenzelm@23252
   228
lemma add_scale_eq_noteq: "\<lbrakk>r \<noteq> r0 ; (a = b) \<and> ~(c = d)\<rbrakk>
wenzelm@23252
   229
  \<Longrightarrow> add a (mul r c) \<noteq> add b (mul r d)"
wenzelm@23252
   230
proof(clarify)
wenzelm@23252
   231
  assume nz: "r\<noteq> r0" and cnd: "c\<noteq>d"
wenzelm@23252
   232
    and eq: "add b (mul r c) = add b (mul r d)"
wenzelm@23252
   233
  hence "mul r c = mul r d" using cnd add_cancel by simp
wenzelm@23252
   234
  hence "add (mul r0 d) (mul r c) = add (mul r0 c) (mul r d)"
wenzelm@23252
   235
    using mul_0 add_cancel by simp
wenzelm@23252
   236
  thus "False" using add_mul_solve nz cnd by simp
wenzelm@23252
   237
qed
wenzelm@23252
   238
chaieb@25250
   239
lemma add_r0_iff: " x = add x a \<longleftrightarrow> a = r0"
chaieb@25250
   240
proof-
chaieb@25250
   241
  have "a = r0 \<longleftrightarrow> add x a = add x r0" by (simp add: add_cancel)
chaieb@25250
   242
  thus "x = add x a \<longleftrightarrow> a = r0" by (auto simp add: add_c add_0)
chaieb@25250
   243
qed
chaieb@25250
   244
haftmann@36712
   245
declare normalizing_semiring_axioms' [normalizer del]
wenzelm@23252
   246
haftmann@36712
   247
lemmas normalizing_semiring_cancel_axioms' =
haftmann@36712
   248
  normalizing_semiring_cancel_axioms [normalizer
haftmann@36712
   249
    semiring ops: semiring_ops
haftmann@36712
   250
    semiring rules: semiring_rules
haftmann@36712
   251
    idom rules: noteq_reduce add_scale_eq_noteq]
wenzelm@23252
   252
wenzelm@23252
   253
end
wenzelm@23252
   254
haftmann@36712
   255
locale normalizing_ring_cancel = normalizing_semiring_cancel + normalizing_ring + 
chaieb@25250
   256
  assumes subr0_iff: "sub x y = r0 \<longleftrightarrow> x = y"
wenzelm@23252
   257
begin
wenzelm@23252
   258
haftmann@36712
   259
declare normalizing_ring_axioms' [normalizer del]
wenzelm@23252
   260
haftmann@36712
   261
lemmas normalizing_ring_cancel_axioms' = normalizing_ring_cancel_axioms [normalizer
wenzelm@23252
   262
  semiring ops: semiring_ops
wenzelm@23252
   263
  semiring rules: semiring_rules
wenzelm@23252
   264
  ring ops: ring_ops
wenzelm@23252
   265
  ring rules: ring_rules
chaieb@25250
   266
  idom rules: noteq_reduce add_scale_eq_noteq
wenzelm@26314
   267
  ideal rules: subr0_iff add_r0_iff]
wenzelm@23252
   268
wenzelm@23252
   269
end
wenzelm@23252
   270
haftmann@36720
   271
sublocale idom
haftmann@36720
   272
  < normalizing!: normalizing_ring_cancel plus times power zero one minus uminus
haftmann@36720
   273
proof
haftmann@36720
   274
  fix w x y z
haftmann@36720
   275
  show "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z"
haftmann@36720
   276
  proof
haftmann@36720
   277
    assume "w * y + x * z = w * z + x * y"
haftmann@36720
   278
    then have "w * y + x * z - w * z - x * y = 0" by (simp add: algebra_simps)
haftmann@36720
   279
    then have "w * (y - z) - x * (y - z) = 0" by (simp add: algebra_simps)
haftmann@36720
   280
    then have "(y - z) * (w - x) = 0" by (simp add: algebra_simps)
haftmann@36720
   281
    then have "y - z = 0 \<or> w - x = 0" by (rule divisors_zero)
haftmann@36720
   282
    then show "w = x \<or> y = z" by auto
haftmann@36720
   283
  qed (auto simp add: add_ac)
haftmann@36720
   284
qed (simp_all add: algebra_simps)
wenzelm@23252
   285
haftmann@36753
   286
declaration {* Semiring_Normalizer.semiring_funs @{thm normalizing.normalizing_ring_cancel_axioms'} *}
wenzelm@23252
   287
haftmann@36712
   288
interpretation normalizing_nat!: normalizing_semiring_cancel
ballarin@29223
   289
  "op +" "op *" "op ^" "0::nat" "1"
huffman@35216
   290
proof (unfold_locales, simp add: algebra_simps)
wenzelm@23252
   291
  fix w x y z ::"nat"
wenzelm@23252
   292
  { assume p: "w * y + x * z = w * z + x * y" and ynz: "y \<noteq> z"
wenzelm@23252
   293
    hence "y < z \<or> y > z" by arith
wenzelm@23252
   294
    moreover {
wenzelm@23252
   295
      assume lt:"y <z" hence "\<exists>k. z = y + k \<and> k > 0" by (rule_tac x="z - y" in exI, auto)
wenzelm@23252
   296
      then obtain k where kp: "k>0" and yz:"z = y + k" by blast
nipkow@29667
   297
      from p have "(w * y + x *y) + x*k = (w * y + x*y) + w*k" by (simp add: yz algebra_simps)
wenzelm@23252
   298
      hence "x*k = w*k" by simp
huffman@35216
   299
      hence "w = x" using kp by simp }
wenzelm@23252
   300
    moreover {
wenzelm@23252
   301
      assume lt: "y >z" hence "\<exists>k. y = z + k \<and> k>0" by (rule_tac x="y - z" in exI, auto)
wenzelm@23252
   302
      then obtain k where kp: "k>0" and yz:"y = z + k" by blast
nipkow@29667
   303
      from p have "(w * z + x *z) + w*k = (w * z + x*z) + x*k" by (simp add: yz algebra_simps)
wenzelm@23252
   304
      hence "w*k = x*k" by simp
huffman@35216
   305
      hence "w = x" using kp by simp }
wenzelm@23252
   306
    ultimately have "w=x" by blast }
wenzelm@23252
   307
  thus "(w * y + x * z = w * z + x * y) = (w = x \<or> y = z)" by auto
wenzelm@23252
   308
qed
wenzelm@23252
   309
haftmann@36753
   310
declaration {* Semiring_Normalizer.semiring_funs @{thm normalizing_nat.normalizing_semiring_cancel_axioms'} *}
wenzelm@23252
   311
haftmann@36712
   312
locale normalizing_field_cancel = normalizing_ring_cancel + normalizing_field
chaieb@23327
   313
begin
chaieb@23327
   314
haftmann@36712
   315
declare normalizing_field_axioms' [normalizer del]
chaieb@23327
   316
haftmann@36712
   317
lemmas normalizing_field_cancel_axioms' = normalizing_field_cancel_axioms [normalizer
chaieb@23327
   318
  semiring ops: semiring_ops
chaieb@23327
   319
  semiring rules: semiring_rules
chaieb@23327
   320
  ring ops: ring_ops
chaieb@23327
   321
  ring rules: ring_rules
chaieb@30866
   322
  field ops: field_ops
chaieb@30866
   323
  field rules: field_rules
chaieb@25250
   324
  idom rules: noteq_reduce add_scale_eq_noteq
wenzelm@26314
   325
  ideal rules: subr0_iff add_r0_iff]
wenzelm@26314
   326
chaieb@23327
   327
end
chaieb@23327
   328
haftmann@36720
   329
sublocale field 
haftmann@36720
   330
  < normalizing!: normalizing_field_cancel plus times power zero one minus uminus divide inverse
haftmann@36720
   331
proof
haftmann@36720
   332
qed (simp_all add: divide_inverse)
haftmann@28402
   333
haftmann@36753
   334
declaration {* Semiring_Normalizer.field_funs @{thm normalizing.normalizing_field_cancel_axioms'} *}
haftmann@28402
   335
haftmann@28402
   336
end